Species of the Poaceae-associated genus Bamboosiella (Thysanoptera, Phlaeothripidae) from China, with three new species - Dang, Li-Hong; Qiao, Ge-Xia (Zootaxa, 2016)
In the Poaceae-associated genus Bamboosiella Ananthakrishnan, eleven species are here recognized from China, including antennatus sp.n. and longisetis sp.n. from Yunnan, and magnus sp.n. from Hainan. Four species are newly recorded from China, bicoloripes Ananthakrishnan, fasciata Okajima, flavescens Okajima and semiflava Okajima. One species from Zhejiang, Bamboosiella brevibristla Sha, Guo, Feng & Duan is placed as a new synonym of B. exastis (Ananthakrishnan & Kudo). An illustrated identification key is provided to the eleven Bamboosiella species now recognised from China.